2022
DOI: 10.1039/d2ra02773a
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-layer coating of MIL-100(Fe) on a cotton fabric for purification of water-soluble dyes by the combined effect of adsorption and photocatalytic degradation

Abstract: A MIL-100(Fe)-based water purifying textile that functions by dual action of adsorption and photocatalytic activity is designed via a layer-by-layer process without using toxic organic solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Figure 7 illustrates the XRD patterns of uncoated, alkali-treated, and Se NP-modified cotton fabric. The strong peaks exhibited in uncoated cotton fabric at 14.5, 16.03, 20.07, 22.8, and 34.7 are characteristic peaks of (101), (101), (012), (002), and (040) reflections of cellulose I in crystalline form, respectively [44]. After alkali treatment, it was observed that diffraction peak (002) became sharper with the KOH activation.…”
Section: Xrdmentioning
confidence: 95%
“…Figure 7 illustrates the XRD patterns of uncoated, alkali-treated, and Se NP-modified cotton fabric. The strong peaks exhibited in uncoated cotton fabric at 14.5, 16.03, 20.07, 22.8, and 34.7 are characteristic peaks of (101), (101), (012), (002), and (040) reflections of cellulose I in crystalline form, respectively [44]. After alkali treatment, it was observed that diffraction peak (002) became sharper with the KOH activation.…”
Section: Xrdmentioning
confidence: 95%